The Genes for Cytoplasmic Ribosomal Ribonucleic Acid in Higher Plants - Scott, N. Steele (1973)
The genes for cytoplasmic ribosomal RNA are partially resolved from the bulk of the DNA by CsCl equilibrium centrifugation. Although in some plants the buoyant density of the ribosomal RNA genes is as expected from the base composition of ribosomal RNA, others show a large discrepancy which cannot be due to the presence of low G-C spacer-DNA. The cross-hybridization observed with 1.3 and 0.7 × 10(6) molecular weight ribosomal RNAs and DNA, which varies greatly with different plant species, is not due to contamination of the ribosomal RNAs, and is specific for the ribosomal DNA of each species, probably largely restricted to those sequences coding for the two stable ribosomal RNAs. The double reciprocal plot may be used for the extrapolation of saturation values only with caution, because in these cases such plots are not linear over the whole of the hybridization reaction.